Developing the Many-Sided Background of the Preschool Children Learning Activities by means of Algorismic Skills Development - L. V. Voronina; Y. A. Utyumova (Russian State Vocational Pedagogical University, 2015)
The paper deals with the current problem of modern education - developing the many-sided background for preschool children's learning activities. At the given stage it is necessary to develop the algorithmic skills - the capability of and readiness for solving different kinds of problems in the strict sequence of operations according to the given patterns. Such algorithmic skills have a meta-disciplinary character and can be developed in class and at home. The paper highlights the algorithmic skills components (personal, regulatory, cognitive and communicative) and the key indicators of their formation. The method for developing the algorithmic skills of preschool children is given including the three age related stages: ability to perform the linear algorithms (middle group), working with the branched cyclic algorithms (senior group), mastering the acquired skills and ability to perform some self- dependent tasks (preparatory group). The paper is addressed to the specialists working in the preschool educational sphere: preschool teachers, methodists, psychologists, directors of kindergartens.